2002
DOI: 10.1007/s00228-002-0425-x
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C19 genotype and S-mephenytoin 4′-hydroxylation phenotype in a Chinese Dai population

Abstract: The frequencies of PMs and CYP2C19*3 allele in the Chinese Dai population are significantly lower than those in the Han population. The CYP2C19 genotype analysis is largely consistent with the mephenytoin phenotype analysis. The variability of S/R ratios in EMs and PMs shows a gene-dosage effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 1 publication
6
22
0
Order By: Relevance
“…In analogy to our results, a clear-cut discrimination between CYP2C19*1/*1 homozygote and *1/*2 heterozygote extensive metabolizers was achieved neither with the S/R-Ratio of mephenytoin 33,41 nor with the omeprazole metabolic ratio. 42,43 Similar finding for several metrics indicate that although homozygous extensive metabolizers may have a slightly higher CYP2C19 activity than heterozygous extensive metabolizers, this difference is probably not relevant for any drug metabolized by CYP2C19.…”
Section: ´-Hydroxymephenytoin Metrics For Cyp2c19 Activitysupporting
confidence: 81%
“…In analogy to our results, a clear-cut discrimination between CYP2C19*1/*1 homozygote and *1/*2 heterozygote extensive metabolizers was achieved neither with the S/R-Ratio of mephenytoin 33,41 nor with the omeprazole metabolic ratio. 42,43 Similar finding for several metrics indicate that although homozygous extensive metabolizers may have a slightly higher CYP2C19 activity than heterozygous extensive metabolizers, this difference is probably not relevant for any drug metabolized by CYP2C19.…”
Section: ´-Hydroxymephenytoin Metrics For Cyp2c19 Activitysupporting
confidence: 81%
“…Among the three studies without genetic information (populations 1, 13, and 14) (Wedlund et al, 1984;Sanz et al, 1989;Bertilsson et al, 1992), the mean of observed ratios ranged twofold (0.18-0.37), and CV values of the ratios were comparable (96-109%). Among the eight studies or 10 populations (populations 2-8 and 10-12) in which only CYP2C19 null alleles were genotyped (Chang et al, 1995;de Morais et al, 1995;Persson et al, 1996;Goldstein et al, 1997;Xiao et al, 1997;Sviri et al, 1999;Aklillu et al, 2002;He et al, 2002), the mean of observed ratios ranged 1.9-, 1.5-, 1.2-, and 1.3-fold for CYP2C19*1/*1 OR *1/*17 OR *17/*17 (0.13-0.23), *1/null OR *17/null (0.21-0.33), null/null (0.97-1.11), and non-PM (0.21-0.29), respectively. Although CV values of the observed ratios were lowered in comparison with those of the three studies without genetic information, they were still high and varied among studies within each genotype, ranging between 57-79, 36-68, 2-7, and 52-70%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen populations investigated in 12 clinical studies of mephenytoin (Wedlund et al, 1984;Sanz et al, 1989;Bertilsson et al, 1992;Chang et al, 1995;de Morais et al, 1995;Persson et al, 1996;Goldstein et al, 1997;Xiao et al, 1997;Sviri et al, 1999;Aklillu et al, 2002;He et al, 2002;Sim et al, 2006) were collated from the data published between 1992 and 2006 using the PubMed online database. Selection criteria included the following: 1) healthy normal adult subjects, 2) a single oral administration of 100 mg racemic mephenytoin, and 3) availability of urinary S/R-mephenytoin ratio at 0-8 hours that were either reported or reasonably recovered by digitization of figures.…”
Section: Pk Modeling and Simulations Of Urinary S/r-mephenytoin Ratiomentioning
confidence: 99%
“…Previous studies carried out by our laboratory have found that interethnic differences with respect to polymorphisms in drug metabolizing enzymes such as CYP2C19 exist between Han and Dai populations. He et al reported that the frequency of the CYP2C19*3 allele in a Dai population was significantly lower than that in a Han population [13] . In the present study, we found that there was no significant difference in the frequencies of the β 1 -adrenoceptor Ser49Gly and Gly389Arg polymorphisms between the two ethnic groups.…”
Section: Discussionmentioning
confidence: 97%
“…The Dai group is the 17-largest ethnic group in China, comprising more than one million people, who live chiefly in the west of Yunnan province, in South-western China [12] . Our previous studies showed that the incidence of drug metabolizing enzyme polymorphisms varies in different ethnic groups [13] . It was therefore interesting to determine whether the incidence of β 1 -adrenoceptor polymorphisms were concordant in 2 different ethnic populations in the same country.…”
Section: Introductionmentioning
confidence: 99%